Phylogenetic analyses of ribosomal transcription units from Haplorchis taichui and H. pumilio species of Heterophyidae (Platyhelminthes: Opisthorchiata) - Viet Ha, Le Thi; Thi Khue, Nguyen; Van Quyen, Dong; Thanh Hoa, Le (Vietnam Journal of Biotechnology, 2021)
Heterophyidiasis caused by minute intestinal flukes becomes of public concern in many countries worldwide. Haplorchis taichui and H. pumilio, belonging to the family Heterophyidae (Platyhelminthes: Trematoda) are two of many infecting humans and commonly found in Vietnam. Sequence study of these two small intestinal flukes is still very limited, hence we need more prospective markers for taxonomic identification and classification. This study provides complete coding sequence of the ribosomal transcription units (rTU) from H. taichui and H. pumilio (Vietnamese samples) and demonstrates the use of complete 28S rDNA sequences for phylogenetic analysis.The complete coding sequence of the rTU (from 5’ 18S to 3’ 28S), consisting of complete 18S, ITS-1, 5.8S, ITS2 and complete 28S rRNA genes and spacers, from H. taichui (7,268 bp) and H. pumilio (7,416 bp) from human hosts in Vietnam, were determined and annotated. The 18S and 5.8S genes of both species were of the same length (1,992 bp/18S, 160 bp/5.8S), but 28S genes differed (3,875 bp/H. taichui and 3,870 bp/H. pumilio). ITS-1 in H. taichui (797 bp) and ITS-2 in H. pumilio (280 bp) do not contain tandem repeat units (TRUs), while ITS-1 in H. pumilio (1,106 bp) contains 3 TRUs of 136 bp/each and 2 TRUs of 116 bp/each and ITS-2 in H. taichui (444 bp) contain 3 TRUs (83–85 bp/each). A phylogenetic tree inferred from the alignment of complete 28S rDNA sequences of 32 trematode strains/species, including 2 Vietnamese Haplorchis spp. and 24 species of 8 families in the suborders Xiphidiata (families Nanophyetidae, Paragonimidae, Collyriclidae), Opisthorchiata (Heterophyidae, Opisthorchiidae), and Echinostomata (Echinostomatidae, Fasciolidae). and Schistosoma japonicum of the family Schistosomatidae is used as an outgroup. The topology of the phylogenetic tree clearly confirmed the status of the Vietnamese H. taichui and H. pumilio species. These species gathered in a group (in the family Heterophyidae) clearly identified in the position of "sister” group to those in the family Opisthorchiidae (suborder Opisthorchiata, superfamily Opisthorchioidea).